Electrochemistry at boron-doped diamond films grown on graphite substrates: redox-, adsorption and deposition processes - Goeting, C; Jones, F; Foord, J; Eklund, J; Marken, F; Compton, R; Chalker, P; Johnston, C (1998)
Highly boron-doped (atomic concentration ∼ 1021 cm-3) conducting diamond films were grown on graphite substrates by microwave assisted vapor deposition from a gaseous feed of hydrogen and methane and solid boron. These diamond films of ca. 5 to 10 μm thickness composed of crystals of up to 10 μm size were characterized by both surface analytical techniques such as Raman spectroscopy, atomic force microscopy (AFM), and scanning electron microscopy (SEM), and electrochemical techniques. The reduction of Ru(NH3)3+6, the oxidation of chlorpromazine, and the reduction of Pb2+ in aqueous media were studied in order to investigate the processes involving oxidation and reduction as well as adsorption and deposition. The one-electron oxidation of chlorpromazine in aqueous 0.1 M KCl and the one electron reduction of Ru(NH3)3+6 in aqueous 0.1 M KCl gave well defined cyclic voltammetric responses at diamond electrodes with peak currents proportional to the square root of the scan rate consistent with diffusion control at a macroscopically uniformly active electrode. For the oxidation of chlorpromazine at concentrations less than 4 mM adsorption of the neutral chlorpromazine at the diamond electrode was additionally detected. At very low scan rates a transition to sigmoidally shaped responses occurred which may be attributed partly to the presence of areas of low or no conductivity on a microscopic level. The reduction of Pb2+ in aqueous 0.1 M HClO4 allowed the deposition of metallic lead on the diamond surface. Studies by ex-situ SEM and in-situ AFM show that Pb nuclei are formed and distributed inhomogeneously over the polycrystalline diamond film in the active surface areas, irrespective of grain boundaries. However, little or no Pb deposition occurred in some less active areas with dimensions of 2 to 100 μm. This effect may be attributed to regions of poor conductivity between the graphite substrate and the diamond film coupled to low lateral conductivity of the film itself. The size of the regions of lower activity decreases with higher applied over-potential. A characteristic delay in the re-dissolution process of the Pb deposit was observed and attributed to both poor adhesion and a resistive contact between deposit and electrode surface. © 1998 Elsevier Science S.A.